Applying Coping Strategies in Classroom Management to Handle Students' Misbehaviour - Sheila Manora Raslinda (Pioneer: Journal of Language and Literature, 2021)
The objective of the study is to discuss the coping strategies to handle students' misbehaviour at a state senior secondary school in South Sumatera. In this study, the researcher investigated how an EFL teacher applied coping strategies in classroom management to handle students' misbehaviour. One teacher was recruited for this study, and semi-structured interview and observational were used in data collection. The study found there are several types of student’s misbehavior that often occured, such as cheating, talkativeness, obtuseness, and inattentiveness. The classification of students’ misbehavior was made in accordance with the research paper of Debreli and Ishanova (2019). However, there are categories not found such as moving around the room, annoying others, and stealing. Coping strategies that are considered most effective to handle students’ misbehavior are talking with students after class, calling the names, and giving praise.